2016
DOI: 10.1038/srep37908
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid-II Independent Antimicrobial Mechanism of Nisin Depends On Its Crowding And Degree Of Oligomerization

Abstract: Nisin inhibits bacterial growth by generating pores in cell membrane and interrupting cell-wall biosynthesis through specific lipid II interaction. However, the role of the hinge region and C-terminus residues of the peptide in antibacterial action of nisin is largely unknown. Here, using molecular dynamics simulations and experimental approach, we report that at high concentration regimes of nisin, interaction with phospholipids may equally deform the bacterial cell membranes even under significantly varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 65 publications
(80 reference statements)
10
71
0
2
Order By: Relevance
“…As with the membrane permeabilization study described above, the possibility that the assay buffer used here affected the CF-301 and/DAP cannot be discounted; however, the very rapid onset of depolarization is consistent with the timing of cell envelope destabilization observed by TEM in Fig. 2 The pore-forming toxin, nisin, was additionally used a positive control because of its ability to rapidly dissipate transmembrane electrostatic potential (31). In Fig.…”
Section: Sub-mic Cf-301 Disrupts Cell Membrane Integritysupporting
confidence: 65%
See 1 more Smart Citation
“…As with the membrane permeabilization study described above, the possibility that the assay buffer used here affected the CF-301 and/DAP cannot be discounted; however, the very rapid onset of depolarization is consistent with the timing of cell envelope destabilization observed by TEM in Fig. 2 The pore-forming toxin, nisin, was additionally used a positive control because of its ability to rapidly dissipate transmembrane electrostatic potential (31). In Fig.…”
Section: Sub-mic Cf-301 Disrupts Cell Membrane Integritysupporting
confidence: 65%
“…Overall, our findings highlight the remarkable potential of this lysin (and possibly the lysin class) to serve as an adjunctive therapeutic strategy used in addition to conventional antibiotics to treat life-threatening bacterial infections, particularly those which result in substantial morbidity and mortality despite treatment with conventional antibiotics. Further studies to elucidate the mechanism(s) of postexposure and sub-MIC effects reported here, including the nature of cell envelope damage, the potential role for induction of the cell wall stress stimulon (31)(32)(33)(34), and the specific impact on cell wall anchored and secreted virulence factors, will be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained considering the mechanisms of action of Nisin. Nisin bactericidal activity is directly related to the oligomerization form of the Nisin for the stabilization of the permeabilizing pores [38]. Thus the amount of Nisin and surface coverage density will be critical to achieve efficient bactericidal activity.…”
mentioning
confidence: 99%
“…Moreover, although in rod-shaped bacteria new peptidoglycan precursors can be added either into their lateral wall or at their division septum, in S. aureus the cell wall biosynthesis occurs predominantly in the division septum, which is rich in lipid II (53, 54). Lipid II is the main target of nisin in bacterial cells that act as an anchor during the pore formation in the cytoplasmic membrane (34, 51, 55). This uneven distribution of lipid II during cell wall biosynthesis in S. aureus was also confirmed with telavancin, a semisynthetic derivative of vancomycin with high affinity to lipid II, which was shown to bind mostly to lipid II in the division septum of exponentially growing S. aureus cells causing membrane depolarization (54).…”
Section: Discussionmentioning
confidence: 99%